Gender Bias Ideologies in Proverbial Discourse - Mohsen , Omar Aziz; Ahmed, Muhammed Badea (Journal of Tikrit University for Humanities, 2023)
The study of gender and language goes beyond just describing the differences between men's and women's linguistic patterns to reveal how language functions as a symbolic method to create and maintain individual, social, and cultural features and identities. Men's and women's linguistic patterns are different, according to research on language and gender. They claim that it is a proven reality caused by unequal and prevalent gender relations.This paper is extracted from the thesis of Ideologies behind Gender Bias in Selected English and Arabic Proverbs: A Pragma-Critical Discourse Analysis, as a prerequisite to be submitted to the Examining Committee.This study investigates the way gender relations are expressed and communicated via the use of English folk proverbs. The major focus of this research is the relationship between language, gender relations, and English culture. As a result, the study focuses on investigating how proverbs play, an important role in gender inequality, and the ideologies that justify them. The research hypothesizes: (1) gender ideologies are manifested discursively and culturally which stand against gender neutrality, (2) gender bias cannot be removed by gender neutrality. The study concludes: (1) that the proverbial discourse shows explicit and implicit ideologies that uphold current gender inequities, (2) gender bias represents the structure of the ideological communities, which is fostered discursively, thus it is an inescapable reality